The EOF of polymer solutions - Olivares, María Laura (2009)
The EOF of polymer solutions is analysed in the framework of continuum fluid mechanics and the standard electrokinetic model. Two key aspects are taken into consideration: the non-Newtonian character of the fluid and the polymer concentration near the interface, which greatly modify the fluid viscosity in the region where electroosmosis takes place. A satisfactory mathematical model is derived for the electroosmotic mobility of solutions that present polymer depletion at the wall. The case of solutions containing polymers that adsorb onto the wall is briefly reviewed, and a preliminary approach is discussed for the limit of strong polymer adsorption. In order to illustrate the theoretical discussions, experimental data obtained from aqueous solutions of carboxymethyl cellulose in fused-silica capillaries are presented. Relevant results are observed, which are appropriately captured by the modelling proposed. The fundamental phenomena discussed in this work are of interest in microfluidics and electrophoresis.